The Phenomenon of Aggression in Kupu-Kupu Seribu Peluru by Agus Noor - Bakti, Jalis Panca (Universitas Padjadjaran, 2024)
Aggression, whether it is indirect, relational, or social, which is directed toward oneself can be a grave danger resulting in a drastic shift in their personality toward negative behaviors. In Kupu-Kupu Seribu Peluru, a short story in the book Cerita buat Para Kekasih by Agus Noor, we can see how the characters interact while affecting one another harmfully. This study explains how aggression works in changing a character’s personality to something they weren’t before, caused by other’s hostility toward them. The purpose of this study is to assess the phenomenon of aggression shown in the short story through literary analysis of the characterization and the narrative structure. It investigates how was the main character’s behavior before she received aggression and what happens after. The findings tell that by only accepting the aggression directed toward her without resistance, the main character alters into a disagreeable individual just as she is accused of in the later part of the story.